Methylphenidate in ADHD and Refractory Epilepsy - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Great Ormond Street Hospital, and Institute of Child Health, London, UK, reviewed the case notes of all patients treated with methylphenidate (MPH) for ADHD at an epilepsy center between 1998 and 2005.